Rekontekstualisasi Konsep Ketuhanan Abd Samad al-Palimbani - Rijal, Syamsul; Umiarso, Umiarso (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2018)
The discourse about God has not been limitedly discussed merely within philosophical and theological dimensions but it has been also discussed within tasawuf approach. A number of Muslim thinkers have so far discussed their understanding of God from this point of view. Abd Samad al-Palimbani was one of the prominent Muslim scholars who tried to discuss the issue of divinity from tasawuf perspective. Al-Palimbani, himself, was a Muslim thinker of 18th century who possessed a specific thought about divinity within such dimension. The approach he employed has become a particularly exceptional matter in the study of divinity in the field. The very basic concept of his thought about God can be observed, among other, within his a monumentally master-piece, entitled Sayr al-S?lik?n. This article seeks to reveal the discourse of divinity discussed in Al-Palimbani?s book. It has been argued that through the concept of martabat tujuh (seven grades), promulgated by Al-Palimbani in his Sayr al-S?lik?n, a s?lik (a seeker of God) will be able to understand and recognize God who possesses W?jib al-Wuj?d as one His attributes. Al-Palimbani?s concept of martabat tujuh undoubtedly puts him as a central figure within the discussion of God and divinity from tasawuf dimension.